Maan rakenteen ja pintavaluntariskien arviointi - Eskelinen, Juha; Alakukku, Laura (MTT, 2004)
Maan rakenne vaikuttaa peltoviljelyn aiheuttamaan ympäristökuormitukseen. Näkyvin seuraus huonosta rakenteesta on veden hidas imeytyminen maahan, mikä lisää pintavalunnan, eroosion ja fosforin huuhtoutumisen riskiä. Hankkeessa seurataan pintavesien esiintymistä viljelytavaltaan erilaisilla lohkoilla. Tavoitteena on muodostaa seurannassa kerättävän ja uusimman tutkimustiedon perusteella käsitys siitä, mitkä ovat tärkeimmät tekijät, jotka lisäävät maan makrohuokostoa ja vähentävät pintavesien esiintymistä. Hankkeessa arvioidaan, miten maatalouden ympäristötuen lisätoimenpiteisiin lukeutuvat keinot (kasvipeitteisyys, kevennetty muokkaus) vaikuttavat maan rakenteeseen ja pintaveden esiintymiseen. Vuonna 2001 ko. lisätoimenpiteeseen sitoutuneita tiloja oli 35 114 kpl, joiden yhteenlaskettu sitoumusala oli 887 400 ha. Hankkeessa on seurattu vuodesta 2001 alkaen maan rakenneongelmia indikoivien märkyysongelmien sekä niistä aiheutuvien kasvuston kellastumisen esiintymistä viljelytavoiltaan erilaisilla Etelä-Suomen savi- ja hiesumailla. Verrattavat viljelymenetelmät ovat kyntö, sänkimuokkaus ja kesantonurmi tai viljelykierto, johon sisältyy nurmea. Tulosten mukaan märkyysongelmia esiintyi keskimäärin eniten sänkimuokattavilla lohkoilla. Niillä lätäköiden ja painanneveden peittämää aluetta oli kaikilla havaintokerroilla keskimäärin 0,48 % lohkoalasta, kun vastaava luku kynnettävillä lohkoilla oli 0,20 % ja heinälohkoilla 0,27 %. Kellastunutta ja harvaa kasvustoa oli sänkimuokattavilla lohkoilla keskimäärin 0,40 %, kynnettävillä 0,10 % ja heinälohkoilla 0,24 %. Tilastollisesti merkitseviä eroja käsittelyjen välillä ei havaittu. Tulosten perusteella suurin pintavalunnan riski oli sänkimuokattavilta lohkoilta. Keskimäärin lätäköiden ja painanneveden peittämää aluetta esiintyi kuitenkin vähän. Lisäksi osaa lohkoista oli siirtymävaiheessa, koska niitä oli sänkimuokattu vähemmän kuin viisi vuotta. Märkyysongelmia aiheutti mm. huonosti toimiva salaojitus ja pellon pinnan vettä keräävä muotoilu.

The objective of the project is to evaluate the effects of agri-environment protection scheme methods (stubble cultivation, crop rotation etc.) on soil structure, surface water occurrence and runoff risk. In 2001, the number of farms committed to crop cover and conservation tillage methods was 35 114 and the total engament area was 887 400 hectares. Project is connected with the parts of agri-environment protection scheme the aim of which is to maintain good soil structure and prevent runoff, erosion and leaching. The effectiveness and suitability of the protection scheme in Finnish conditions are evaluated on the grounds of the results of this project and research knowledge. In the present project the existence of areas covered by surface water, ponding water and wet soil were observed on the fields of 13 private farms in 2001-03. Also the areas of sparse or yellow growth and without vegetation were observed. These are considered as indicators of poor soil structure. The farms located on clay and silt soils in southern and southwestern Finland. Each farm had 3 fields where cultivation methods 1) conventional tillage (CT), 2) conservation tillage (RT) and 3) grass fallow or crop rotation including ley (Grass) were compared. The treatments were: (CT) the plot was supposed to be ploughed annually; (RT) the plot was supposed to be treated according to the regulations based on the Agri-Environmental programme, in practice chiselling or no tillage, and (Grass) grass fallow or crop rotation including ley, for example dry hay or seed production, no pasture or silage. The average slope of the plots varied usually between 0-2 %, the slope of one CT-plot was about 4 %. The area of indicating poor soil structure was determined by satellite positioning. The areas suffering form excess water were classified as surface water (area completely covered by water), ponding water (area partly covered by water) and wet soil (the soil is completely saturated by water, but no water exists at the top of the soil). Observations were made each year in spring after snow was melt away, every year in June-July, in September 2001, and in November-December 2001 and 2003. No observations were made in the end of 2002 because of drought. During each observational period either all or selected farms were observed. The functioning of drainage system has been noted since 2002. The coverage of areas suffering from excess water was largest in RT, which means the most extensive surface runoff risk, too. Statistically significant differences between the treatments were not found when testing each observational period separately. On the average of the period 2001-03 the area covered by surface water and ponding water together was 0.48 % for the treatment RT, while the coverage for CT was 0.20 %, and for Grass 0.27 %. The area of sparse or yellow growth and without vegetation was 0.40 % in RT, 0.10 % in CT, and 0.24 % in Grass. The mean coverage areas were, however, small. The coverage of the problem areas existing repeatedly at the same positions during different observational periods behaved similarly. Some of the RT fields were in transition period (conservation tillage period less than 5 years) which might affect the results.
Keywords: Ka; ympäristö; maan rakenne; pintavalunta; kyntö; kevennetty maanmuokkaus; viljelykierto; ympäristötuki; kuormitus; suorakylvö; soil structure; surface runoff; conventional tillage; ploughing; conservation tillage; stubble cultivation; crop rotation; GPS